The Dynamic Interplay Between Cardiac Inflammation and Fibrosis - Thomas, Toby P.; Grisanti, Laurel A. (Frontiers in Physiology, 2020)
Heart failure is a leading cause of death worldwide. While there are multiple etiologies contributing to the development of heart failure, all cause result in impairments in cardiac function that is characterized by changes in cardiac remodeling and compliance. Fibrosis is associated with nearly all forms of heart failure and is an important contributor to disease pathogenesis. Inflammation also plays a critical role in the heart and there is a large degree of interconnectedness between the inflammatory and fibrotic response. This review discusses the cellular and molecular mechanisms contributing to inflammation and fibrosis and the interplay between the two.